The effects of a 12-week combined motor control exercise and isolated lumbar extension intervention on lumbar multifidus muscle stiffness in individuals with chronic low back pain - Tornblom, Audrey; Naghdi, Neda; Rye, Meaghan; Montpetit, Chanelle; Fortin, Maryse (Frontiers in Physiology, 2024)
Introduction: Exercise therapy is the primary endorsed form of conservative treatment for chronic low back pain (LBP). However, there is still conflicting evidence on which exercise intervention is best. While motor control exercise can lead to morphological and functional improvements of lumbar multifidus muscle in individuals with chronic LBP, the effects of exercise prescription on multifidus stiffness assessed via shear wave elastography are still unknown. The primary aim of this study is to determine the effects of a combined motor control and isolated lumbar extension (MC+ILEX) intervention on lumbar multifidus muscle stiffness. Methods: A total of 25 participants aged 18 to 65 were recruited from local orthopedic clinics and the university community with moderate to severe non-specific chronic LBP. Participants performed a 12-week MC+ILEX intervention program. Stiffness of the lumbar multifidus muscle (primary outcome) at L4 and L5 was obtained at baseline, 6-week, and 12-week using shear wave elastography. Changes in stiffness ratio (e.g., ratio of lumbar multifidus muscle stiffness from rest to contracted) were also assessed at both time points. Pre to post-intervention changes in lumbar multifidus muscle stiffness were assessed using a one-way repeated measure ANOVA. Results: Following the 12-week intervention, there were no statistically significant changes in lumbar multifidus muscle stiffness at rest on the right side at L4 (p = 0.628) and the left side at L4 and L5 (p = 0.093, p =0.203), but a statistically significant decrease was observed on the right side at L5 (p= 0.036). There was no change in lumbar multifidus muscle stiffness ratio. Conclusion: This study provides preliminary evidence to suggest that a 12-week MC+ILEX intervention had minimal effect on lumbar multifidus muscle stiffness in individuals with chronic LBP. Further investigations are needed to confirm our findings and clarify the relationship between muscle stiffness and functional outcomes.